Increasing the Activity of Students in the Process of Learning in Mathematics and the Role of Didactic Games - Alimdjanovna, Mamajonova Mahira (International Journal on Integrated Education, 2024)
Three articles discuss the importance of didactic games in the process of teaching mathematics and determining the activity of students in the classroom.